The picture of visual evoked potentials in type 2 diabetes mellitus - Szabela, Dariusz A.; Loba, Jerzy; Pałenga-Pydyn, Dorota; Tybor, Krzysztof; Ruxer, Jan; Split, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of this study was to assess frequency of abnormal visual evoked potentials in type 2 diabetic patients and the correlation between patients' age, duration of the disease, metabolic control and coexisting clinical complications on the abnormal recordings. 41 diabetic patients, aged 35 to 62 years were examined. The VEP recordings were performed four times, each time using a pattern made up of elements of another size (18, 36, 72 and 144 angular minutes). With this method the abnormal VEP were recorded in 22% of the cases. The abnormal VEP recordings with a single size pattern were in 8% to 14% of the cases. The P100 latency increased in 33% of the pathological recordings and in about 66% of the cases there was a significant difference between the latencies from both eyes. There was no statistically significant correlation between the age, duration of the disease, coexisting clinical complications or metabolic compensation and the abnormal recordings.